The Study of Potential Antiviral Compounds from Indonesian Medicinal Plants as Anti-COVID-19 with Molecular Docking Approach - Baiq Ressa Puspita Rizma; Agus Dwi Ananto; Anggit Listyacahyani Sunarwidhi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Corona Virus Disease 2019 (COVID-19) is a new strain of coronavirus called SARS-CoV-2, which was identified in Wuhan, China, in December 2019. The rapid transmission of COVID-19 from human to human forced researchers to find a potent drug by setting aside the time-consuming traditional method in drug development. The molecular docking approach is one a reliable method to screening compound from chemical drug or by finding a compound from Indonesian herbal plants. The present study aimed to assess the potency of compounds from five medicinal plants as potential inhibitors of PLpro and 3CLpro from SARS-CoV-2 using molecular study. The molecular docking was performed using Protein-Ligand Ant System (PLANTS) to analyze the potential compounds by the docking score. Remdesivir triphosphate was used as a standard for the comparison of the test compounds. The docking score obtained from the docking of PLpro with native ligand, remdesivir triphosphate, curcumin, demethoxycurcumin, bisdemethoxycurcumin, luteolin, apigenin, quercetin, kaempferol, formononetin-7-O-glucuronide, andrographolide, and neoandrographolide were -111.441, -103.827, -103.609, -102.363, -100.27, -79.6655, -78.6901, -80.9337, -79.4686, -82.1124, -79.1789, and -97.2452, respectively. Meanwhile, docking score with 3CLpro for the same ligand were -64.0074, -86.1811, -81.428, -87.1625, -78.2899, -73.4345, -70.3368, -71.5539, -68.4321, -72.0154, -75.9777, and -93.7746. The docking score data suggest that curcumin was the most potential as a PLpro inhibitor, while neoandrographolide was the best as a 3CLpro inhibitor.